Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan Di PT Pegadaian Pada Kantor Daerah Pemeriksaan Bojonegoro Provinsi Jawa Timur Yang Dimediasi Oleh Semangat Kerja - Bambang Sutanto; Akbar Wicaksono; Bayu Ariyadi; Dian Aditya Kusuma; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
Bambang Sutanto, 2025. The Influence of Transactional Leadership on Employee Work Performance in the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province, Mediated by Work Spirit. Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 65 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To prove and analyze whether organizational culture has a direct influence on the work performance of employees at the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province. 2) To prove and analyze whether organizational culture has a direct influence on the work spirit of the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province. 3) To prove and analyze whether work discipline has a direct influence on the work performance of employees at the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province. 4) To prove and analyze whether work discipline has a direct influence on the work spirit of the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province. 5). To prove and analyze whether work enthusiasm has a direct influence on the work performance of employees at the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province 6) To prove and analyze whether organizational culture has an indirect influence on employee work performance which is mediated by work morale at the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province78) To prove and analyze whether work disciplines has an indirect influence on employee work performance which is mediated by work morale at the PT. Pegadaian at the Bojonegoro Regional Inspection Office, East Java Province. The research results show that: 1) organizational culture does not have a significant positive effect on employee work performance as evidenced by the original sample value of 0.280 and p-values ​​of 0.058. 2) organizational culture has a significant positive effect on work morale as evidenced by the original sample value of 0.377 and p-values ​​of 0.015. 3) Work morale has a significant positive effect on employee work performance as evidenced by the original sample value of 0.557 and p-values ​​of 0.000. 4) Transactional leadership has a significant positive indirect effect on employee work performance and work morale as evidenced by the original sample value of 0.210 and p-values ​​of 0.022.